2014
DOI: 10.11622/smedj.2014177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of faecal incontinence in the community: a cross-sectional study in Singapore

Abstract: INTRODUCTIONFaecal incontinence (FI) is frequently referred to as a 'silent epidemic', explaining the inherent difficulty in obtaining reliable data that is reflective of the study population. FI is a socially stigmatised condition that is extremely distressing to its sufferers, and a cause of both physical and psychological morbidity. While sufferers from all age groups have been reported, FI is known to predominantly affect the elderly.(1) The predicament of this group of patients is worsened by the embarras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 19 publications
0
11
0
6
Order By: Relevance
“…Prevalence rates ranged from 1⋅4 to 19⋅5 per cent 15 -44 . All but five studies 23,24,30,32,42 were able to give 95 per cent confidence intervals within 2 per cent of the FI prevalence estimate. Included studies were heterogeneous with regard to minimum age of recruitment, response rate, study methodology and study definition.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Prevalence rates ranged from 1⋅4 to 19⋅5 per cent 15 -44 . All but five studies 23,24,30,32,42 were able to give 95 per cent confidence intervals within 2 per cent of the FI prevalence estimate. Included studies were heterogeneous with regard to minimum age of recruitment, response rate, study methodology and study definition.…”
Section: Resultsmentioning
confidence: 86%
“…Nine studies included various severity scales in their definitions, including: Faecal Incontinence Severity Index (FISI), St Mark's tool by Vaisey and colleagues, the Wexner score by Miller et al ., and one developed by Bharucha and colleagues. Despite use of comparable severity scores, estimated prevalence rates varied widely (1·5–17·0 per cent), likely reflecting the heterogeneity of stool type and frequency definitions used by the different studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] The incidence of fecal incontinence based on sex is controversial. 4,5 However, examination of anal function using manometry has shown a difference in fecal incontinence associated with age, as well as sex. 2,3 In contrast, other reports have suggested that fecal incontinence is more common in women than in men.…”
Section: Introductionmentioning
confidence: 99%
“…En la literatura internacional existe una gran variabilidad y discordancia con respecto al tema, dependiendo de la población y método de estudio utilizado, sin embargo, un rango entre 2 y 18% en población general es lo más aceptado 4,[10][11][12][13][14][15][16][17] . Encontramos un estudio de Zárate et al, del año 2008, que presenta una prevalencia de IF a gases de un 20,5% y a sólidos y líquidos de un 2,7%…”
Section: Introductionunclassified